Manipulating chain type and flail drum speed for better fibre recovery in chain-flail delimber-debarker-chipper operations - Spinelli, Raffaele (Array, 2019)
A chain-flail delimber-debarker-chipper (CFDDC) was adapted for treating smaller trees than normal by replacing the standard flails with lighter ones, and by reducing flail drum rotation speed. The machine produced 16 full containers (24 t each) for the standard configuration and 24 full containers for the innovative one. For each container the researchers measured: original tree mass, chip mass, time consumption and fuel use. Results indicated that the innovative setting accrued a 12% improvement on fiber recovery compared with the standard setting (control). At the same time, productivity increased by 20% and fuel consumption was reduced by 30%. Product quality was largely unaffected, with bark content remaining below the 1% threshold specification. If at all, product quality was improved through the reduction of fine particles, possibly derived from less diffused fraying. These results have triggered the real scale adoption of the new setting by contractors who participated in the study. The success of the innovative treatment is likely explained by its better alignment with the weaker structure of small trees from low-yielding stands.